2003
DOI: 10.1046/j.1439-0426.2003.00441.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and product quality of European eel (Anguilla anguilla) as affected by dietary protein and lipid sources

Abstract: Summary A 12‐week feeding trial was undertaken to evaluate the effects of partial replacement of marine raw materials in the diet with soybean meal and beef tallow on growth and product quality of European eel (Anguilla anguilla). Based on growth, feed efficiency and chemical composition, soybean meal was found to be an unsuitable ingredient for eel diets as a substitute for fishmeal (25% on a protein basis), probably because of the low digestibility of its carbohydrate content. However, beef tallow can be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
5
18
1
Order By: Relevance
“…Generally, fat deposits increase with weight irrespective of the feeding; for example, larger fish tend to have higher lipid content. This has already been shown for gilthead sea bream [4], eel [5], catfish species [6], carp [7], and salmonids [8][9][10].…”
Section: Feeding and Its Impact On Fish Fatsupporting
confidence: 55%
See 1 more Smart Citation
“…Generally, fat deposits increase with weight irrespective of the feeding; for example, larger fish tend to have higher lipid content. This has already been shown for gilthead sea bream [4], eel [5], catfish species [6], carp [7], and salmonids [8][9][10].…”
Section: Feeding and Its Impact On Fish Fatsupporting
confidence: 55%
“…Thus, there is a preferable deposition in the muscle fat for certain species, such as flatfish [13,34], while other species, such as perch, preferably accumulate fat in the peritoneum [28]. Some species also follow a completely different pattern of fat deposition, such as cod that tend to accumulate the dietary fat almost exclusively as liver fat [26,35], and the adult eel, where feeding seems to have almost negligible impact because main muscle fat deposition occurs earlier during its development [5]. However, contradictory results have been found, even within the same species, with respect to the effects of feeding rate, dietary lipids, and starvation, in the fish fat deposits.…”
Section: Feeding Intensity and Dietary Fatmentioning
confidence: 99%
“…Replacing fish oil with tallow had little effect on fish body composition. This is in agreement with observations from other studies using beef tallow as alternative lipid source (Greene and Selivonchick 1990; Craig and Gatlin 1995; Luzzana et al 2003; Xue et al 2006). Using tallow also did not affect carcass yield, HSI, and fillet proximate composition in this study.…”
Section: Discussionsupporting
confidence: 93%
“…Some studies suggested that diets containing rendered fats, such as tallow, may not be able to support optimal growth performance (Murai et al 1985; Fracalossi and Lovell 1994, 1995; Fracalossi et al 1994). However, a number of studies reported that partially replacing fish oil with saturated lipid source, specifically, beef tallow, does not affect growth and FE as long as adequate levels of unsaturated FAs are supplied and the essential fatty acid (EFA) requirements are met (Stickney and Andrews 1971; Yu and Sinnhuber 1981; Greene and Selivonchick 1990; Craig and Gatlin 1995; Reigh and Ellis 2000, Luzzana et al 2003; Xue et al 2006). In the present study, replacing 50% fish oil with tallow did not affect TGC or FE.…”
Section: Discussionmentioning
confidence: 99%
“…trash fish (TF), slaughterhouse waste (SW), pelleted trout feed (PF), and combination of them (TF+PF and SW+PF) only have daily growth of 0.21±0.01, 0.32±0.03, 0.29±0.01, 0.30±0.17, and 0.0.36±0.23 g respectively. [21] use different sources of diet, diet from fish (CB) source seems to be effective to give better weight gain instead of combination between fish and beef tallow (BT) or fish with soybean (SB). The results show that the CB give 42% absolute growth, while BT and SB only 37 and 30 % respectively.…”
Section: Weight Gainmentioning
confidence: 99%